THE EFFECT OF GEOGEBRA-ASSISTED CREATIVE PROBLEM SOLVING ON COMPUTATIONAL THINKING ABILITY REVIEWED FROM SELF CONFIDENCE - Sri Agustini Dalimunthe; Yurniwati; Nurjannah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Computational thinking is an innovative thinking ability in identifying life phenomena to provide various practical solutions to the problems studied. The research conducted aims to analyze students' computational thinking abilities based on high and low levels of self-confidence. This study aims to investigate the impact of the Creative Problem Solving (CPS) Learning Model assisted by GeoGebra on elementary school students' computational thinking abilities. An experimental method with a posttest-only control group design was used, employing Cluster Random Sampling to select a sample of 120 students. The research instrument consisted of a computational thinking ability test, which was analyzed using a t-test with SPSS software. The t-test results showed a significant difference in computational thinking abilities between the experimental group and the control group. The findings indicate that Geogebra-assisted CPS significantly improves the computational thinking skills of elementary school students, proven to be more effective than the expository model.